Pemanfaatan Citra Digital dalam Bidang Kesehatan: Tinjauan Literatur - Mohamad Idris; Linda Septiani (Medula, 2026)
The development of digital technology has driven significant transformation in healthcare, particularly through the utilization of digital imaging. The application of digital imaging in healthcare includes disease diagnosis, radiological analysis, early disease detection, identification of herbal medicinal plants, patient monitoring, telemedicine, and the development of Artificial Intelligence (AI)-based healthcare systems to enhance the accuracy and efficiency of medical services. This study examined the utilization of digital imaging in healthcare based on various relevant studies. The method used in this study was a literature review conducted by collecting and analyzing national and international scientific articles related to digital image processing in healthcare. The results of the literature review indicate that digital imaging plays an important role in improving the effectiveness of diagnosis, medical analysis, and telemedicine services. Artificial Intelligence (AI) technologies, particularly deep learning and Convolutional Neural Networks (CNN), have demonstrated high accuracy in medical image processing, while image compression technology improves the efficiency of medical data transmission. However, its implementation still faces several challenges, including limitations in technological infrastructure, image quality, internet connectivity, and patient data security. Therefore, the development of digital imaging technology in healthcare needs to be continuously improved to support a more optimal healthcare system. Keywords: artificial intelligence, digital imaging, medical diagnosis, healthcare, technology